(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Literacy enhances people’s knowledge and abilities. Literacy as a fundamental human right is becoming more widely recognized across the globe. Because of this, learning never ends. Having skill makes any task easier to do. Practical education builds on previously gained information, and the two go hand in hand. Making a student financially independent is one of the primary goals of formal education. College degrees are a boon to society in many ways, both financially and otherwise. A total of eleven general secular colleges spread across ten districts in Dehradun were considered for the selection. A large percentage, around 73%, of the population was represented by these institutions. Similarly, twenty private institutions were selected at random from the whole population, making up around 40% of the total. Included were the heads of all 31 universities. The researchers selected a total of 405 professors using the simple random sampling method. Of these, 176 worked for public universities, or about 38% of the total, while 229 were employed by private universities, or about 42% of the total. In a similar vein, 459 pupils were given the test/questionnaire. Of these kids, 230 (or 3.48% of the total) were associated with public schools, while 229 (or 1.54% of the total) were attached to private ones.